(untitled) (Damu Journal of Sport Sciences, 2025)
Modern playing methods have varied and diversified, resulting in differences in individual and collective defensive and offensive plans. These tactics require a high and distinct level of skill performance during more complex situations that require speed, accuracy, struggle, and continuous movement throughout the match, with maximum efficiency for all players. Therefore, the primary concern of coaches during attacks should be to try to reach the opposing team's goal with the least possible effort and at the greatest possible speed, in order to score the greatest number of goals. The current research aims to: Develop a training curriculum using compound skill performances for U19 youth soccer players for the research sample. To identify the impact of the training curriculum using complex skill performances on the skill performance level of the youth soccer players in the research sample. The researcher used the experimental method using a single-group design with a pre- and post-test method. The research sample consisted of (18) youth players from the Diyala Sports Club. The results obtained revealed statistically significant differences in the complex skill performances and skill performance levels, in favor of the post-test. The researcher attributes this development to the training curriculum applied to the research sample. The researcher concluded: There were statistically significant differences between the pre- and post-test measurements in the skill performance level, in favor of the post-tests. There were also clear improvement rates for the research sample members. The training curriculum had a positive impact on the skill performance level for all basic skills applied in the training curriculum.